2020
DOI: 10.3390/ijms21165906
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Emerging Role of Prolidase in Cellular Metabolism

Abstract: Prolidase [EC 3.4.13.9], known as PEPD, cleaves di- and tripeptides containing carboxyl-terminal proline or hydroxyproline. For decades, prolidase has been thoroughly investigated, and several mechanisms regulating its activity are known, including the activation of the β1-integrin receptor, insulin-like growth factor 1 receptor (IGF-1) receptor, and transforming growth factor (TGF)-β1 receptor. This process may result in increased availability of proline in the mitochondrial proline cycle, thus making proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 101 publications
(182 reference statements)
0
37
0
Order By: Relevance
“…Given our data, it cannot be excluded that the described manifestation of PD may derive from a deficiency of extracellular PEPD function since supplementation of PD patients with proline or proline-convertible amino acids was ineffective in the therapy of the disease [ 51 ]. New data on the role of PEPD as a regulator of p53 function, interferon-α/β receptor maturation, and activation of EGFR or HER2 create the prospect of discovering new functions of PEPD [ 30 ]. As our study evidenced promising effects of PEPD in cell proliferation, migration, and connective tissue rearrangement (mainly on collagen biosynthesis), further experiments are crucial to understanding its role in PD and other connective tissue disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our data, it cannot be excluded that the described manifestation of PD may derive from a deficiency of extracellular PEPD function since supplementation of PD patients with proline or proline-convertible amino acids was ineffective in the therapy of the disease [ 51 ]. New data on the role of PEPD as a regulator of p53 function, interferon-α/β receptor maturation, and activation of EGFR or HER2 create the prospect of discovering new functions of PEPD [ 30 ]. As our study evidenced promising effects of PEPD in cell proliferation, migration, and connective tissue rearrangement (mainly on collagen biosynthesis), further experiments are crucial to understanding its role in PD and other connective tissue disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Growth promoting and anabolic pathways require activation of integrin receptor pathways. For instance, stimulation of β 1 -integrin receptor induces autophosphorylation of FAK that integrates the signal from growth factor receptors leading to up-regulation of two MAP kinases: ERK1/2 [ 28 , 29 ] inducing cell growth, differentiation, and metabolism [ 28 , 30 ]. Of special interest is that activation of β 1 -integrin receptor up-regulates PEPD activity and collagen biosynthesis [ 8 , 9 , 12 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolidase and prolinase are the only known enzymes that are capable of hydrolyzing proline-containing dipeptides, also called iminodipeptides, into free proline. Prolidase such as peptidase D (PEPD) specifically hydrolyzes C-terminal proline, while prolinase such as dipeptidyl peptidase IV (DPP4) and its family, specifically cleaves off N-terminal proline (Misiura and Miltyk 2020;Waumans et al 2015). In addition to collagen, many bioactive peptides contain proline to protect them from unexpected degradation.…”
Section: Sources Of Free Prolinementioning
confidence: 99%
“…An increase in prolidase activity supports proline availability for collagen biosynthesis. Of special interest is the ability of extracellular PEPD to interact directly with the epidermal growth factor receptor (EGFR), inducing EGFR-dependent signaling [ 16 ]. Moreover, recent reports have indicated that PEPD can bind p53, protecting its translocation to the nucleus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the tissue specificity of prolidase, the highest level of prolidase mRNA expression is observed in the kidneys, small intestine, and duodenum [ 18 ], while high prolidase activity has been reported in erythrocytes and human skin fibroblasts [ 19 ]. Guszczyn et al [ 1 ] showed that PRP is an important source of prolidase [ 16 ], however, its role in wound healing is not known. Since prolidase evokes several anabolic activities, we hypothesized that it is an important player in the mechanism of the PRP-dependent wound healing process in an experimental model of human keratinocytes.…”
Section: Introductionmentioning
confidence: 99%